2016
DOI: 10.3390/ijms17111809
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol Affects Oxidative Stress, Cholesterol Homeostasis and the Amyloidogenic Pathway in Neuroblastoma Cells: Consequences for Alzheimer’s Disease

Abstract: One of the characteristics of Alzheimer´s disease (AD) is an increased amyloid load and an enhanced level of reactive oxidative species (ROS). Vitamin E has known beneficial neuroprotective effects, and previously, some studies suggested that vitamin E is associated with a reduced risk of AD due to its antioxidative properties. However, epidemiological studies and nutritional approaches of vitamin E treatment are controversial. Here, we investigate the effect of α-tocotrienol, which belongs to the group of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 88 publications
0
42
0
Order By: Relevance
“…Saito and co-authors reported that αTF and αT3 attenuated cell death induced by glutamate using primary cortical neurons isolated from cerebral cortex of Sprague-Dawley rats fetuses [276]. Another in vitro study using human neuroblastoma (SH-SY5Y) cells found that αTF and αT3 decreased cholesterol and ROS like hypochlorite (-OCl) and free hydroxyl radical (OH) as vitamin E had been proposed to have cholesterol-lowering and antioxidant effects [277]. However, the study also revealed enhanced Aβ production and reduced Aβ degradation in αT3-treated cells [277].…”
Section: Effects Of Tocotrienol On Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Saito and co-authors reported that αTF and αT3 attenuated cell death induced by glutamate using primary cortical neurons isolated from cerebral cortex of Sprague-Dawley rats fetuses [276]. Another in vitro study using human neuroblastoma (SH-SY5Y) cells found that αTF and αT3 decreased cholesterol and ROS like hypochlorite (-OCl) and free hydroxyl radical (OH) as vitamin E had been proposed to have cholesterol-lowering and antioxidant effects [277]. However, the study also revealed enhanced Aβ production and reduced Aβ degradation in αT3-treated cells [277].…”
Section: Effects Of Tocotrienol On Neurodegenerative Diseasesmentioning
confidence: 99%
“…Another in vitro study using human neuroblastoma (SH-SY5Y) cells found that αTF and αT3 decreased cholesterol and ROS like hypochlorite (-OCl) and free hydroxyl radical (OH) as vitamin E had been proposed to have cholesterol-lowering and antioxidant effects [277]. However, the study also revealed enhanced Aβ production and reduced Aβ degradation in αT3-treated cells [277]. This side effect of T3 should be considered when initiating treatment in Alzheimer's disease subjects.…”
Section: Effects Of Tocotrienol On Neurodegenerative Diseasesmentioning
confidence: 99%
“…In other cellular models, such tocopherol as tocotrienol isomers has been studied regarding its capacity to protect cells from an oxidative challenge. For instance, 24 h preincubation with α-tocopherol or α-tocotrienol showed no differences in avoiding ROS generation in SH-SH5Y cells subjected to 1 µM H 2 O 2 for 40 min [26]. In cerebellar granular cells, on the other hand, 5 µM α-, γ-tocotrienol showed axonal and dendritic protection from structural damage induced by 0.5 µM H 2 O 2 (24 h) with some differences in the level of lipid peroxidation induced by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 93%
“…However, recent notable discoveries concerning TCT in over 900 published research articles in PubMed have established that this micronutrient, found abundantly in palm oil and barley, provides some health benefits not offered by TCP. Remarkably, TCT isomers have been shown to have more profound anti-oxidative, cholesterol lowering and anti-cancer effects than TCP [3][4][5]. Consequently, more investigators are now beginning to examine the benefits of TCT.…”
Section: Tocotrienols As Antioxidantsmentioning
confidence: 99%